Factors Affecting Recurrence among Patients with Stroke, La-ngu District, Satun Province - Jaranai, Paleeya; Nawsuwan, Kittiporn (Princess of Naradhiwas University Journal, 2025)
This descriptive research using case control study aimed to determine factors affecting recurrence among patients with stroke, La-ngu district, Satun province. Sample were 128, divided into 64 of cases (recurrent stroke) and 64 of controls (post stroke) admitted to inpatient department of La-ngu hospital, Satun province. Research instruments consisted of demographic recording form and a set of questionnaires including knowledge of warning signs, perceived susceptibility, food consumption behavior, exercise, medication adherence, follow-up and alcohol drinking and cigarette smoking. IOC ranged from .67 to 1.00 and Cronbach alpha coefficient reliability of each of questionnaire was .710, .738, .773, .722, .748, .711 and .745 respectively. Data were analyzed using descriptive statistics and multiple logistic regression analysis. Research results were found as follows; Factors affecting recurrence among patients with stroke La-ngu district, Satun province at significance levels of .01 and .001 included duration of stroke (ORadj=71.09, 95%CI: 10.74-471.72), knowledge of warning signs (ORadj=8.27, 95%CI: 1.90-35.95), perceived susceptibility of recurrence (ORadj=87.95, 95%CI: 1.73-36.61) and appropriate food consumption (ORadj=26.76, 95%CI: 5.51-130.01). Hence, to reduce the chance of recurrent stroke, activities promoting knowledge of warning signs and perceived susceptibility of recurrence should be provided to patients as well as promoting food consumption behavior and continuous monitoring in those who had more than 1 year of disease duration.